Cost‐utility analysis of magnetoencephalography used to inform intracranial electrode placement in patients with drug resistant epilepsy: a model based analysis. Issue 6 (8th June 2016) - Berrigan, Patrick; Bardouille, Tim; MacLellan, Matt; Mohamed, Ismail S; Murthy, Manjari
Abstract: Objectives: We estimated the cost‐effectiveness of adding magnetoencephalography to a standard assessment for epilepsy surgery consisting of neuropsychology, magnetic resonance imagining, scalp electroencephalography, video electroencephalography and intracranial electroencephalography, in the capacity of informing intracranial electroencephalography electrode placement. Methods: We used Microsoft Excel (2007) to construct a decision model. Discounted costs and quality adjusted life years are aggregated to calculate incremental cost‐effectiveness ratios. Sensitivity analyses are conducted to assess robustness of findings. Results: Our base case analysis yielded a result of 14 300 per quality adjusted life year gained. A total of 82.7% of probabilistic sensitivity analysis iterations resulted in incremental cost‐effectiveness ratios below 100 000 in 2014 Canadian dollars. Conclusions: Our findings demonstrate that the inclusion of Magnetoencephalography in the assessment for epilepsy surgery in the capacity of informing intracranial electroencephalography electrode placement is likely not cost saving but does represent a reasonable allocation of resources from a value for money perspective.